2020
DOI: 10.1103/physrevb.101.115127
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon interaction and zero-field charge carrier transport in the nodal-line semimetal ZrSiS

Abstract: We study electron-phonon interaction and related transport properties of nodal line semimetal ZrSiS using first-principles calculations. We find that ZrSiS is characterized by a weak electronphonon coupling of the order of 0.1, which is almost energy-independent. Main contribution to the electron-phonon coupling originates from long-wavelength optical phonons, causing no significant renormalization of the electron spectral function. At the charge neutrality point, we find that electrons and holes provide a com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…To obtain a quantitative understanding of the oscillation frequencies described above, additional information on the FS is needed. However, the nodal-line semimetal-lic nature of ZrSiS makes its FS structure very sensitive to the exact position of the Fermi level, which is partly the reason for the apparently different FS reported in earlier DFT calculations 16,28,29 . Among the resolvable peaks (γ, β 1 and β 2 ) summarized in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…To obtain a quantitative understanding of the oscillation frequencies described above, additional information on the FS is needed. However, the nodal-line semimetal-lic nature of ZrSiS makes its FS structure very sensitive to the exact position of the Fermi level, which is partly the reason for the apparently different FS reported in earlier DFT calculations 16,28,29 . Among the resolvable peaks (γ, β 1 and β 2 ) summarized in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…where σ i 's (i = x, z) are the Pauli matrices, m ≈ 0.1 − 1 m e (m e is the mass of an electron) is the effective mass [34,44,45], ∆ ≈ 0.1 − 1 eV is the energy scale that defines the nodal loop radius [46,47] and v F ≈ 10 5 −10 6 m/s is the Fermi-velocity in the z direction [44,45]. Diagonalizing the Hamiltonian yields the energy spectrum as E ± (p) = ±ε p with ± the band index and…”
Section: Model Hamiltonian and Observablesmentioning
confidence: 99%
“…It is defined as E z,c = /(ev F τ 2 sc ) for z direction and E x,c = 2m /(e 2 τ 3 sc ) for x direction. The scattering time is estimated as τ sc ∼ 10 −2 − 10 −1 ps [45,66], which implies that the minimal electric field required to observe nonlinear transport is E x/z,c ∼ 10 5 − 10 7 V/m. For E E > E x/z,c , the current changes its slope as a function of the electric field, but an even larger electric field window may be required to obtain the corresponding exponents.…”
Section: Experimental Possibilitiesmentioning
confidence: 99%
“…ZrXY family of materials where X = Si, Sn, Ge and Y = S, Se, Te are among the most studied TNSMs due to their high crystal quality and flexibility of the chemical composition [9,10,[27][28][29][30][31][32][33][34][35][36][37][38][39]. Among the ZrXY family of materials, ZrSiS is an especially interesting material, since it possesses linearly dispersing bands extending up to 2 eV, which are free from interference from trivial bands making this material an excellent prospect for studying Dirac physics [27].…”
mentioning
confidence: 99%
“…ZrXY family of materials where X = Si, Sn, Ge and Y = S, Se, Te are among the most studied TNSMs due to their high crystal quality and flexibility of the chemical composition [9,10,[27][28][29][30][31][32][33][34][35][36][37][38][39]. Among the ZrXY family of materials, ZrSiS is an especially interesting material, since it possesses linearly dispersing bands extending up to 2 eV, which are free from interference from trivial bands making this material an excellent prospect for studying Dirac physics [27]. Even though several experimental studies have been reported on ZrSiS such as angle-resolved photoemission spectroscopy (ARPES) [9,10,30,37,38], high-field magnetotransport measurements [40,41], scanning tunneling microscopy [42], frequency-independent optical conductivity [43], high carrier mobility [41,44], the experimental and theoretical description of the effect of phonon scattering in electron cooling processes have not been studied so far.…”
mentioning
confidence: 99%